GOOD GOVERNANCE IN THE PERSPECTIVE OF MALAY CUSTOMS AND THE QUR'AN - Muhammad Ilham; Mastikawati (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2021)
Abstract: This article focused on good governance in the perspective of Malay customs and the Koran. This article aimed to understand; the concept of good governance according to Malay customs and the Qur'an. Utilizing library sources (Library Research) to obtain data from reading materials that are accurate and relevant to the research discussion, and identify the data according to the steps, then proceed with analyzing the data using the Tafsir al-Adabiy al-Ijtima'i (socio-cultural) Thematic Tafsir methodology. This study concluded that good governance according to Malay customs contains the principles of good governance according to cos and the construction of good governance is manifested in seloko, and good governance does not conflict with the spirit of the Qur'an and al-Hadith. The principle of good governance in Jambi Malay customs is identical to the principle of governance in the Qur'an.